BaDBL1, a unique DREB gene from desiccation tolerant moss Bryum argenteum, confers osmotic and salt stress tolerances in transgenic Arabidopsis. (December 2021) - Liang, Yuqing; Li, Xiaoshuang; Yang, Ruirui; Gao, Bei; Yao, Juanxia; Oliver, Melvin J.; Zhang, Daoyuan
Highlights: A unique DREB transcription factor from Bryum argenteum was characterized. Overexpression of BaDBL1 in Arabidopsis increases antioxidant capacity. The accumulation of lignin was modulated by BaDBL1 . BaDBL1 is a positive regulator involved in regulation of plants tolerance to osmotic and salt stresses. Abstract: The dehydration-responsive element-binding (DREB) transcription factors play important roles in regulation of plant responses to abiotic stresses, however, few DREBs have been isolated from a desiccation tolerance moss, and the role of DREBs in the DT mechanism is still unknown. We have functionally characterized a unique DREB transcription factor BaDBL1 from the DT moss Bryum argenteum . Expression pattern analysis revealed that BaDBL1 was induced by dehydration-rehydration, salt, cold, and abscisic acid treatments. BaDBL1 was localized in the nucleus and had a transactivation region in its C-terminal region. Overexpression of BaDBL1 in Arabidopsis resulted in significantly increased osmotic and salt stress tolerance, as illustrated by higher fresh weight and antioxidase activities (SOD, POD and CAT) compared with WT under osmotic and salt stresses. Moreover, the transcription of stress-responsive genes, such as AtRD29A and AtCOR15A, AtLEA in BaDBL1 -overexpressing lines were significantly up-regulated under osmotic and salt stresses compared with WT. Transcriptomic analysis revealed that BaDBL1 -overexpression affected the lignin biosynthesis pathway by improving lignin content and regulating lignin-biosynthesis-related genes under osmotic stress. The results suggest that BaDBL1 may regulate plant tolerance to stress by enhancing anti-oxidase activities, regulating expression of stress-related genes and effecting the lignin biosynthesis, making BaDBL1 a candidate gene for stress tolerance improvement in crops.